Relação entre deformação a frio, microestrutura e comportamento mecânico da liga Ti35Nb2,5Sn - Santos, Silvando Vieira dos (2019)
This study aims to evaluate the correlation between cold deformation, heat treatment, microstructure and mechanical properties of the Ti35Nb2.5Sn alloy, the application of which is of interest to the industry for the manufacturing of various components. The Ti35Nb2.5Sn alloy was produced by arc fusion, cold rolled with reductions of 70%, 80% and 90% and underwent heat treatments of solubilization at a temperature of 900 ° C for 15 min and / or aging at the temperature of 350 ° C for times of (2, 6, 24, 44, 72 and 96) h. Microstructural characterization was achieved by optical microscopy and X-ray diffraction. Mechanical properties evaluation was performed using Vickers hardness tests, tensile tests, flexural fatigue tests and fatigue tests. The microstructural characterization of the Ti35Nb2,5Sn alloy confirmed the presence of the β, α '' and ω phases. From the different levels of reduction in the cold rolling it was shown that Vickers hardness values did not obtain differences. Through the tensile and flexion tests, it was verified that the higher the level of deformation, the greater the resistance of the material. The effects of the aging treatment for 24 h after cold rolling promoted increase of hardness, strength and loss of ductility. For the fatigue tests, it was verified that the aging promoted a 41.7% and 58.3% increase in the fatigue strength limits for the cold rolling reduction levels of 70% and 90%, respectively.